Wheat rust makes a comeback - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
The telltale reddish brown spores that herald a resurgence of wheat s most deadly pathogen have been spotted on plants in Ethiopia, Kenya and Uganda...